2018
DOI: 10.1007/s00167-018-5119-8
|View full text |Cite
|
Sign up to set email alerts
|

Injury incidence in semi-professional football claims for increased need of injury prevention in elite junior football

Abstract: Salaried semi-professional football involves a high overall injury incidence. The highest incidence, particularly of overuse injuries, was seen in elite junior football. These findings should be incorporated in specific injury prevention training or screenings beginning in junior football. Level of evidence II.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

4
5

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 37 publications
2
21
0
1
Order By: Relevance
“…Injury distribution is similar to that in amateur and professional soccer, thus indicating a similar need for injury prevention strategies. 20,21 Beside traumatic injuries, this study also investigated overuse pain and complaints during and after the bubble-soccer tournament. For the first time, this study showed a high percentage of players with head and neck pain as well as knee pain.…”
Section: Discussionmentioning
confidence: 99%
“…Injury distribution is similar to that in amateur and professional soccer, thus indicating a similar need for injury prevention strategies. 20,21 Beside traumatic injuries, this study also investigated overuse pain and complaints during and after the bubble-soccer tournament. For the first time, this study showed a high percentage of players with head and neck pain as well as knee pain.…”
Section: Discussionmentioning
confidence: 99%
“…One part of those screening tests was the application of psychological tests. After the screening tests, a prevention intervention programme was applied 2. The study was conducted in collaboration with the Regional Football Association Bayern (1.6 million players, largest regional Football Association under the German Football Association) and the Public Trauma Insurance for elite salaried athletes in Germany, Verwaltungsberufsgenossenschaft.…”
Section: Methodsmentioning
confidence: 99%
“…Even though soccer is very popular, it is also accompanied by a high risk of injuries. The prevalence of at least one injury in one season in the semiprofessional German salaried soccer leagues was 79% 2. Besides the topic of injury risk and injury prevention in soccer, the possible relevance of mental health problems, that means emotional or psychological, gets more and more prominent because of the tragic suicide of famous soccer players and because of the statements of national players that the high pressure in professional soccer leads to symptoms of anxiety and depression.…”
Section: Introductionmentioning
confidence: 99%
“…In soccer adult players, 60-80% of such lesions are located on the lower extremities especially the knees and ankles [4][5][6][7][8][9][10]. In adult athletes, the lumbar region is the most common vertebral lesion site [11]. Chronic lesionsthose that occur due to excessive use of the joints-are the most common [12,13].…”
Section: Introductionmentioning
confidence: 99%